2019
DOI: 10.3390/nu11051125
|View full text |Cite
|
Sign up to set email alerts
|

Choline and DHA in Maternal and Infant Nutrition: Synergistic Implications in Brain and Eye Health

Abstract: The aim of this review is to highlight current insights into the roles of choline and docosahexaenoic acid (DHA) in maternal and infant nutrition, with special emphasis on dietary recommendations, gaps in dietary intake, and synergistic implications of both nutrients in infant brain and eye development. Adequate choline and DHA intakes are not being met by the vast majority of US adults, and even more so by women of child-bearing age. Choline and DHA play a significant role in infant brain and eye development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 134 publications
(162 reference statements)
0
45
0
Order By: Relevance
“…However, the increase in obesity during pregnancy and breastfeeding as well as gestational diabetes, among other pathologies observed during the last decade, could alter the transport of LCPUFA to the placenta leading to a decrease in LCPUFA (mainly DHA) availability [ 72 , 74 , 75 ]. Currently, the potential impact in brain development of the transport of LCPUFA to the fetus or to the infant in maternal obesity and/or gestational diabetes, is a main study objective [ 71 , 75 ], findings that justify LCPUFA intake recommendations during pregnancy and lactation [ 71 , 75 , 76 ].…”
Section: Dha and Aa During Pregnancy And Breast Milk Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase in obesity during pregnancy and breastfeeding as well as gestational diabetes, among other pathologies observed during the last decade, could alter the transport of LCPUFA to the placenta leading to a decrease in LCPUFA (mainly DHA) availability [ 72 , 74 , 75 ]. Currently, the potential impact in brain development of the transport of LCPUFA to the fetus or to the infant in maternal obesity and/or gestational diabetes, is a main study objective [ 71 , 75 ], findings that justify LCPUFA intake recommendations during pregnancy and lactation [ 71 , 75 , 76 ].…”
Section: Dha and Aa During Pregnancy And Breast Milk Periodmentioning
confidence: 99%
“…AA levels showed a strong inverted U function in response to increased DHA supplementation when neural development was evaluated, i.e., at the highest DHA containing formula (0.96%) (DHA:AA ratio 1.5:1.0); it was observed that AA decreased in the blood, as compared to the two low and intermediate formulas (0.32% and 0.64% DHA) [ 92 ]. Today is a standard procedure the fortification of infant formulas with DHA and EPA, which are added as triglycerides, phospholipids, or fatty acid concentrates [ 76 ].…”
Section: Dha and Aa In Brain Developmentmentioning
confidence: 99%
“…For this reason, choline has been recognized as an essential nutrient, because a supplementary intake by foods is necessary. Modern diet does not seem to provide a sufficient intake of choline (RDA: 550 and 425 mg/day for men and women, respectively) [87,88]. In analogy with other methyl donors, also choline deficiency results in HHcy and epigenetic dysregulation of genes controlled through methylation.…”
Section: Cholinementioning
confidence: 99%
“…Infants received enough choline and LC-PUFAs from breast milk, which are very important for the brain, retinal and neurovisional development. In another study, it was emphasized that formula foods containing choline and LC-PUFAs were required for growth and development in non-breastfed infants [64].…”
Section: Breastfeeding and Retinal Diseasementioning
confidence: 99%